Prenatal diagnosis of ornithine transcarbamylase deficiency: optimizing pregnancy outcome in a woman with previous affected babies - Galidevara, Chandana; Chandrasekaran, Swaramya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Ornithine Transcarbamylase (OTC) deficiency is an inherited X-linked disorder which predominantly affects males. Females are usually carriers and may rarely be symptomatic. Affected individuals may present with severe life threatening disease immediately after birth. Those with variants of the disease may have late adult onset symptoms. We report a case of an asymptomatic female heterozygous carrier of the defect with recurrent poor obstetric outcomes and subsequent management with prenatal diagnostic testing.